SnO2 thin film structural properties and optical characteristics (Eurasian Research Bulletin, 2025)
This paper examines the structural and optical properties of thin-film nanoparticles based on tin dioxide (SnO2). SnO2 is an n-type semiconductor with a wide band gap (3.6–3.8 eV), widely used in gas sensors, photocatalytic, and optoelectronic devices. In this study, SnO2 nanoparticles were obtained using sol-gel and thermal evaporation methods, and their structure and morphology were studied using X-ray diffraction, atomic force microscopy, and scanning electron microscopy. X-ray diffraction data from the tetragonal phase of the films showed that the polycrystalline structure has a similar structure. Annealing at elevated temperatures (200–600 °C) resulted in sharpening of diffraction peaks, increased crystallinity, and increased particle size. AFM and SEM analyses revealed grain size in the range of 76–98 nm, i.e., temperature increases with surface flatness improvement. Optical analysis revealed SnO₂ films exhibiting high transmittance (≈90%) and low reflectivity, which supports this function. The study demonstrated that results from SnO₂-based films in gas sensors, solar cells, and optoelectronics applications can be recommended as a promising material